Pengaruh Komunikasi Interpersonal Dan Iklim Organisasi Terhadap Kinerja Guru Sekolah Minggu Buddha (SMB) Maitreya Di Indonesia - Merita Merita; Ida Ayu Gde Yadnyawati; Lianah The; Muljadi (Dhammavicaya : Jurnal Pengkajian Dhamma, 2022)
This study uses multiple regression analysis to examine the effect of interpersonal communication and organizational climate on the teacher performance of Maitreya Buddhist Sunday School in Indonesia. In this study the determination of the sample using the census method or total sampling with a total sample of 105 respondents. This study uses primary data, data is collected by distributing questionnaires to respondents via google forms. The results of the study show that: (1) interpersonal communication has a positive and significant effect on the teacher performance of Maitreya SMB in Indonesia with a correlation coefficient score of 0.758, a determination coefficient of 0.575; (2) Organizational climate has a positive and significant effect on the teachers performance of Maitreya SMB in Indonesia with a correlation coefficient score of 0.732, a coefficient of determination of 0.536; (3) Interpersonal communication and organizational climate have a positive and significant effect together on the teacher performance of SMB school in Indonesia with a correlation coefficient score of 0.827, a coefficient of determination of 0.684. Based on the results of the study, to optimize teacher performance, policies and regulations are needed to improve interpersonal communication and organizational climate.